THE IMPORTANCE OF SMART URBAN PLANNING FOR THE CONSTRUCTION OF SMARTS CITIES - Narciso de Oliveira, Everton (Journal of Interdisciplinary Debates, 2022)
This article has smart cities as its theme and aims to identify the role and importance of urban planning as an instrument for the realization of smart cities. This research is bibliographical and presents the historical context of urban planning as well as concepts of sustainability, security and egalitarian distribution within this scenario, advancing to the concepts of smart cities, their definitions and how they relate to urban planning. The study presents and reflects on the importance of the smart urban planning tool as a protagonist for the construction of really effective smart cities in the promotion of sustainable, safe cities that provide well-being for their inhabitants.